Effectiveness of Gradient Boosting Stacking Model in Predicting Electricity Costs: Residential Building Data - Nadifa, Ulfatun; H, Haeriani; Abdussamad, Syahrir; Tolago, Ade Irawaty; Dako, Rahmat Deddy Rianto; Bonok, Zainudin; Asmara, Bambang Panji (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Accurate electricity cost prediction is essential to support energy efficiency and resource management, particularly in residential and commercial buildings. This study aims to evaluate the effectiveness of the Gradient Boosting model in predicting monthly electricity costs. The model is built using the Stacking Ensemble method, a technique that combines multiple Gradient Boosting algorithms in a layered manner to improve prediction accuracy. To enhance the model’s performance, automatic selection of the best parameter values (Hyperparameter Optimization) is conducted using Optuna. The initial phase involves developing a tree-based preprocessing pipeline to address data variability and complexity. The model is evaluated using the K-Fold Cross Validation method, which divides the data into several subsets for more representative testing. The performance is assessed using the Root Mean Squared Logarithmic Error (RMSLE) metric to measure prediction accuracy. The evaluation results show that the model achieves an RMSLE score of 0.22, with an average prediction time of 0.00029 seconds. These findings suggest that although Gradient Boosting models are typically used on high-dimensional datasets, this approach remains effective for low-dimensional data. The combination of ensemble techniques and hyperparameter optimization yields accurate and efficient predictions. Therefore, this approach can be applied in real-world scenarios, such as urban energy management.Prediksi biaya listrik yang akurat penting untuk mendukung efisiensi energi dan pengelolaan sumber daya, terutama pada bangunan residensial maupun komersial. Penelitian ini bertujuan untuk menguji efektivitas model Gradient Boosting dalam memprediksi biaya listrik bulanan. Model dibangun dengan menggunakan metode Stacking Ensemble, yaitu teknik penggabungan beberapa algoritma Gradient Boosting secara bertingkat untuk meningkatkan akurasi prediksi. untuk meningkatkan kinerja model, digunakan pemilihan nilai parameter terbaik secara otomatis (Optimasi Hyperparameter) dengan bantuan Optuna. Tahapan awal dimulai dengan membangun pipeline preprocessing berbasis Tree Model untuk menangani variasi dan kompleksitas data. Model dievaluasi dengan menggunakan metode K-Fold Cross Validation, yaitu pembagian data menjadi beberapa bagian untuk pengujian yang lebih representatif, dan hasilnya diukur menggunakan metrik Root Mean Squared Logarithmic Error (RMSLE) untuk menilai ketepatan prediksi. Hasil evaluasi menunjukkan bahwa model mampu mencapai nilai RMSLE sebesar 0.22. Selain itu, waktu prediksi rata-rata adalah 0.00029 detik. Temuan ini menunjukkan bahwa meskipun model Gradient Boosting umumnya digunakan pada dataset berdimensi besar, pendekatan ini tetap efektif pada data berdimensi kecil. Kombinasi teknik ensemble dan Optimasi Hyperparameter mampu menghasilkan prediksi yang akurat dan efisien. Oleh karena itu, pendekatan ini dapat diterapkan dalam skenario nyata, seperti manajemen energi di kawasan perkotaan.